2010
DOI: 10.1007/s10658-010-9699-5
|View full text |Cite
|
Sign up to set email alerts
|

Tomato leaf deformation virus, a novel begomovirus associated with a severe disease of tomato in Peru

Abstract: Begomovirus infection was suspected in tomato plants exhibiting symptoms of curling and deformation of leaves observed in a survey conducted in northern and central Peru. Rolling circle amplification and restriction fragment length polymorphism analyses suggested that a begomovirus was present in symptomatic plants. The full-length sequence of a begomovirus DNA component was determined, comprising 2591 nucleotides. Based on its genome organization, we suggest it corresponds to the DNA-A of a New World begomovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
2
20
1
1
Order By: Relevance
“…Finally, no DNA-B component was detected in DNA gel blot hybridization analyses of total genomic DNA from the ToLCD samples collected in Peru in 1998, whereas the expected hybridization signal was detected in total genomic DNA from N. benthamiana leaves infected with the bipartite begomovirus BDMV (data not shown). Together, these results indicated that ToLCD in Ecuador and Peru is associated with a single begomovirus genomic DNA, and our results are in agreement with the results of Marquez-Martin et al (26).…”
Section: Toldev Is Associated With Tolcd In Peru Andsupporting
confidence: 93%
See 3 more Smart Citations
“…Finally, no DNA-B component was detected in DNA gel blot hybridization analyses of total genomic DNA from the ToLCD samples collected in Peru in 1998, whereas the expected hybridization signal was detected in total genomic DNA from N. benthamiana leaves infected with the bipartite begomovirus BDMV (data not shown). Together, these results indicated that ToLCD in Ecuador and Peru is associated with a single begomovirus genomic DNA, and our results are in agreement with the results of Marquez-Martin et al (26).…”
Section: Toldev Is Associated With Tolcd In Peru Andsupporting
confidence: 93%
“…Based upon the known genome structure of NW begomoviruses, it was presumed that ToLDeV would have a bipartite genome (26). The finding that ToLDeV isolates associated with ToLCD in Ecuador and Peru have a single genomic DNA, with no associated DNA-B component or satellite DNAs, confirmed and extended the results of Marquez-Martin et al (26) and indicated an unconventional etiology for the disease. Here, we established that ToLDeV is an indigenous NW monopartite begomovirus and is the causal agent of ToLCD in Ecuador and Peru.…”
Section: Tolcd In Ecuador Andmentioning
confidence: 57%
See 2 more Smart Citations
“…In the last few years, an increasing number of reports of novel begomovirus species, new hosts and geographical distribution of begomoviruses have occurred in Latin America (NavasCastillo et al, 2011). In Peru, isolates of two begomovirus species have been reported, euphorbia mosaic Peru virus (EuMPV) found infecting a sample of the weed Euphorbia heterophylla L. collected in the Machu Picchu region in 2007, for which the complete DNA-A of one isolate is available (Shepherd et al, 2008), and ToLDeV, a monopartite begomovirus found infecting tomato crops throughout the major tomato-growing areas of this country at least since 1998 (Márquez-Martín et al, 2011;Melgarejo et al, 2013;Sánchez-Campos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%